ECONOMIC ASPECTS OF GEO&EKO MARKETING IN TOURISM - Liudmila Guzikova; Aleksandr Kolesnikov (Вестник Северо-Кавказского федерального университета, 2022)
In thepaper the role of the tourism sector in the economy and the financial and economic indicators characterizing this role for the country, region, territory are analyzed. Interrelation of financial and economic results of tourism and state of geographical and ecological environmentis substantiated. Economic Principles geo & eko marketing are formulated. Recommendations to control tourist flows based on these principles are worked out.